2017
DOI: 10.1371/journal.pone.0173883
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and histopathologic findings after pars plana vitrectomy with a new hypersonic vitrector system. Qualitative preliminary assessment

Abstract: PurposePreliminary assessment of a new prototype ultrasound-based hypersonic vitrector (HV) by qualitatively examining the histopathological changes in the retina and vitreous body after pars plana vitrectomy (PPV) and its ability to fragment vitreous collagen.MethodsFourteen porcine cadaveric eyes, 20 eyes in live swine and six human cadaveric eyes underwent PPV using the HV or a pneumatic guillotine vitrector (GV). An additional 4 porcine crystalline lenses were touched with either the HV or GV for 1 minute.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
2
16
0
3
Order By: Relevance
“…3 ). This LC location is consistent with previous reports in porcine eyes, 9 , 17 19 and corresponded to a region of higher echogenicity within the ONH in the ultrasound images. A division of the ONH into anterior and posterior halves showed the LC present within the anterior half of the ONH in both the ultrasound and histology images.…”
Section: Resultssupporting
confidence: 92%
“…3 ). This LC location is consistent with previous reports in porcine eyes, 9 , 17 19 and corresponded to a region of higher echogenicity within the ONH in the ultrasound images. A division of the ONH into anterior and posterior halves showed the LC present within the anterior half of the ONH in both the ultrasound and histology images.…”
Section: Resultssupporting
confidence: 92%
“…This study is the follow up to the ultrastructural and histopathological findings after pars plana vitrectomy (PPV) in cadaveric porcine and human eyes and non-delay live porcine eyes. In our previous study, light microscopy and electron microscopy showed similar morphological changes in the retina, vitreous and crystalline lens after PPV [ 2 ]. The HV have also produced consistent water and vitreous flow rates across the range of stroke length and aspiration levels [ 3 ].…”
Section: Introductionmentioning
confidence: 72%
“…The described US tissue damage includes global biomechanical properties alteration, histo-morphological changes, protein denaturation and tissue necrosis [ 10 – 14 ]. In our previous work, comparison between the control eyes, porcine and human cadaveric eyes that had PPV with GV or HV had histopathological findings primarily at the inner retinal layers, with some degree of vacuolization and fragmentation in the NFL and GCL, as well as internal limiting membrane (ILM) separation [ 2 ]. These changes are similar in this study 30 days following PPV with either the HV or GV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, hypersonic vitrectomy systems have been introduced in which a handpiece, the hypersonic vitrectomy probe (HVP), produces high-frequency longitudinal vibrations with the aim of inducing vitreous liquefaction close to the tip. 6,7 The potential advantages of HVPs are related to probe design and mechanism of action. With regard to the former, in a GVP the inner needle moves inside the outer one, determining the cyclic port opening and closing, whereas in the HVP there is a single needle and the port is always open.…”
Section: Introductionmentioning
confidence: 99%